Conceptual framework of service-based learning moderating effect on the relationship between students’ knowledge of ethics course content and generic skill - Muhamad, Haslinah; Mustapha, Mazlina; Soh, Wei Ni; Ong, Tze San (Human Resource Management Academic Research Society, 2021)
SULAM, a service-based learning approach, was launched on the 13th of April 2019 by the Ministry of Education Malaysia, and the Institute of Higher Learning (IHLs) in Malaysia began to respond to it as part of the new competency requirements. The School of Business and Economics (SBE) at Universiti Putra Malaysia is genuinely active in integrating community service activities in their programs including accounting degrees. Since the Accounting program is said to give very little attention on instilling values, ethics, and integrity, it has been proposed to integrate SULAM into the accounting program to particularly enhance generic skills. Among the subject that is suitable to integrate this approach are Business Ethics and Corporate Governance. Corporate Social Responsibility can be chosen as a proxy of the service-based learning approach. Based on the experiential learning theory, this paper offers the conceptual framework regarding the moderating effect of CSR experiential learning approach (as a proxy of SULAM) in the relationship between the theory of knowledge on ethics and generic skill enhancement for future studies. Knowledge in the course contents will become an independent variable (theory of knowledge) including the concept of CSR and human governance. CSR activity is a moderator and generic skill including emotional intelligence as an extra element will be treated as a dependent variable. The knowledge of course content propose to be measured by a questionnaire or test given to students (pre-test, before being involved in the CSR activities), CSR activities can be measured by types such as philanthropy, environment conservation, diversity and labor practices, and volunteerism. The dependent variable which is a generic skill can be measured by performance in post-test for enhancing of knowledge or questionnaire with the same participants or evaluation made by a coordinator in certain industrial players.